Synthesis and Characterization of Some New D-mannose Derivatives Containing 1, 2, 3-Triazole Moiety and Screening Their Action as Urease Inhibitors - Zeyad Kadhim Oleiwi (Journal of Global Pharma Technology, 2018)
Williamson etherification of (1) with propargyl bromide afforded the 1-O-propargyl-2, 3:5, 6-Di-O-isopropyli-dene α-D-mannofuranoside (2) in a very good yield. 1, 3-Dipolar cycloaddition of (2) with four different aryl azides derivatives using click conditions gave four new 1, 2, 3-triazole derivatives containing sugar moiety. The biological activity of synthesized compounds were tested against urease activity by immobilize this enzyme on the synthesized compounds. All of these compounds show inhibition activity of enzyme. Some of these compounds (T1) show high inhibition action on the enzyme activity, while (T2, T3, T4) show moderate effect on the activity.Keywords: Mannose, Derivatives, 1, 2, 3-triazole, Urease, Inhibitors.